2014
DOI: 10.1002/14651858.cd006424.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Culturally appropriate health education for people in ethnic minority groups with type 2 diabetes mellitus

Abstract: Culturally appropriate health education has short- to medium-term effects on glycaemic control and on knowledge of diabetes and healthy lifestyles. With this update (six years after the first publication of this review), a greater number of RCTs were reported to be of sufficient quality for inclusion in the review. None of these studies were long-term trials, and so clinically important long-term outcomes could not be studied. No studies included an economic analysis. The heterogeneity of the studies made subg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
154
2
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(175 citation statements)
references
References 176 publications
6
154
2
1
Order By: Relevance
“…Managing chronic diseases in a diverse population necessitates culturally appropriate education and care, 9 which highlights diabetes among Muslims during Ramadan as well as fasting practices in other religions. 17 Fortunately, given the wealth of information and studies from other countries, there is a foundation to create quality improvement projects focused on education, knowledge, and awareness of both health providers and patients regarding diabetes management during Ramadan in the United States.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Managing chronic diseases in a diverse population necessitates culturally appropriate education and care, 9 which highlights diabetes among Muslims during Ramadan as well as fasting practices in other religions. 17 Fortunately, given the wealth of information and studies from other countries, there is a foundation to create quality improvement projects focused on education, knowledge, and awareness of both health providers and patients regarding diabetes management during Ramadan in the United States.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Therefore, many providers are not aware of the specific issues regarding diabetes care during Ramadan; nor do they properly counsel or educate their patients with diabetes who fast. This further emphasizes the need for culturally appropriate health education for different ethnic groups, 9 who may fast for religious purposes. Given the absence of studies specifically in the United States, the purpose of this pilot study was to better understand provider practices and knowledge of diabetes care during Ramadan for Muslim patients in an inner-city primary care clinic in New York City to identify areas to educate and improve provider awareness.…”
Section: Introductionmentioning
confidence: 99%
“…13 Culturally appropriate education is effective in both short-and medium-term performance measures (HbA 1c reduced by 0.4% and 0.5%, respectively). 14,15 Neither LDL nor HDL was lowered in these interventions.…”
Section: Discussionmentioning
confidence: 83%
“…A 2014 Cochrane review showed that glycemic control and knowledge of diabetes are improved when culturally appropriate health education is provided to people with diabetes who belong to ethnic minority groups. 39 Peer health coaches might be providing more culturally appropriate health education in ethnic minority populations, particularly Latino ones.…”
Section: Discussionmentioning
confidence: 99%